PERUBAHAN pH SALIVA SISWA MA DARUL ISTIQAMAH MANADO SESUDAH MENYIKAT GIGI DENGAN PASTA GIGI MENGANDUNG XYLITOL - Najoan, Stevy B.; Kepel, Billy J.; Wicaksono, Dinar A. (Universitas Sam Ratulangi, 2014)
Abstract: Saliva plays a role in the occurrence of dental caries. The low of buffer capacity and secretion of saliva leads to reduced salivary ability in wash away food particles, deadly micro organisms and neutralize the salivary pH. Changes in the salivary pH is influenced by circadian rhythms, the type of food consumed, stimulation of salivary secretion, salivary flow rate, micro organisms of the oral cavity and salivary buffer capacity. Xylitol is a sweetener similar to polyols that are non-acidogenic and non-cariogenic. Xylitolis difficult to be fermented by bacteria in the oral cavity so can help to increasing the decreases of salivary pH due the consumption of foods containing carbohydrates. In the field of dentistry, xylitol has been applied in a wide range of products such as chewing gums, lozenges, mouth washes and toothpastes. This study was conducted to determine the salivary pH before brushing teeth with tooth paste containing xylitol, the salivary pHafter brushing teeth with tooth paste containing xylitol and the changes of salivary pH after brushing teeth with tooth paste containing xylitol. The research design used was analytics experimental pretest and posttest design. The population used were 56 students of MA Darul Istiqamah Manado. Sampling was done by using simple random sampling technique with 20 samples were obtained by matched-pair research formula. Saliva collection methodsused werethe spittingmethod. The results showed a change in the salivary pH after brushing teeth with tooth paste containing xylitol. The average value ofthe salivary pH after brushing teeth with tooth paste containing xylitol were 7,18 higher than the average value of the salivary pH before brushing teeth with tooth paste containing xylitol were 6.99. Results of statistical tests of paired-samples t-test showed that there were significant differences (p <0.05) of the salivary pH before and after brushing teeth with tooth paste containing xylitol. Conclution: Xylitol has a role in increasing the salivary pH which helps in inhibiting dental caries. Keywords: salivary pH, brushing teeth, toothpaste containing xylitol. Abstrak: Saliva berperan dalam proses terjadinya karies gigi. Rendahnya sekresi dan kapasitas bufer saliva menyebabkan berkurangnya kemampuan saliva dalam membersihkan sisa makanan, mematikan mikroorganisme serta menetralkan pH saliva. Perubahan pH saliva dipengaruhi oleh irama sirkadian, jenis makanan yang dikonsumsi, stimulasi sekresi saliva, laju aliran saliva, mikroorganisme rongga mulut dan kapasitas bufer saliva. Xylitol merupakan sejenis pemanis polyols yang bersifat non-asidogenik dan non-kariogenik. Xylitol sulit untuk difermentasi oleh bakteri dalam rongga mulut sehingga dapat membantu dalam meningkatkan pH saliva yang turun akibat konsumsi makanan yang mengandung karbohidrat. Dalam bidang kedokteran gigi, xylitol telah banyak diaplikasikan dalam berbagai macam produk seperti permen karet, tablet hisap, obat kumur dan pasta gigi. Penelitian ini dilakukan untuk mengetahui pH saliva sebelum menyikat gigi dengan pasta gigi mengandung xylitol, pH saliva sesudah menyikat gigi dengan pasta gigi mengandung xylitol dan perubahan pH saliva sesudah menyikat gigi dengan pasta gigi mengandung xylitol. Rancangan penelitian yang digunakan yaitu analytic experimental pretest and posttest design. Populasi yang digunakan yaitu siswa MA Darul Istiqamah Manado yang berjumlah 56 orang. Pengambilan sampel dilakukan dengan teknik simple random sampling dengan jumlah sampel yang didapatkan yaitu 20 orang berdasarkan rumus penelitian dua populasi berpasangan. Metode pengumpulan saliva yang digunakan yaitu spitting method. Hasil penelitian menunjukkan terjadi perubahan pH saliva sesudah menyikat gigi dengan pasta gigi mengandung xylitol. Nilai rata-rata pH saliva sesudah menyikat gigi dengan pasta gigi mengandung xylitol yaitu 7,18 lebih tinggi dari nilai rata-rata pH saliva sebelum menyikat gigi dengan pasta gigi mengandung xylitol yaitu 6,99. Hasil uji statistik paired-samples t-test memperlihatkan bahwa terdapat perbedaan yang bermakna (p<0,05) pH saliva sebelum dan sesudah menyikat gigi dengan pasta gigi mengandung xylitol. Simpulan: xylitol memiliki peran dalam meningkatkan pH saliva sehingga dapat mencegah terjadinya karies gigi. Kata kunci: pH saliva, menyikat gigi, pasta gigi mengandung xylitol